2007
DOI: 10.1109/mcs.2007.909465
|View full text |Cite
|
Sign up to set email alerts
|

Power Kites for Wind Energy Generation [Applications of Control]

Abstract: T he problems posed by electric energy generation from fossil sources include high costs due to large demand and limited resources, pollution and CO 2 production, and the geopolitics of producer countries. These problems can be overcome by alternative sources that are renewable, cheap, easily available, and sustainable. However, current renewable technologies have limitations. Indeed, even the most optimistic forecast on the diffusion of wind, photovoltaic, and biomass sources estimates no more than a 20% cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, the near-ground wind is highly dependent on the geography and weather. Recent studies have shown that these limitations can be eliminated by developing high-altitude wind power technology. Compared with near-ground wind, the advantages of high-altitude wind energy include fast speed, wide distribution, high stability, and perenniality . Meanwhile, high-altitude platforms (HAPs), situated at altitudes 17–22 km above the ground, have the capability of providing services and applications ranging from broadband wireless access, navigation and positioning systems, and remote sensing to weather observation/monitoring systems .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the near-ground wind is highly dependent on the geography and weather. Recent studies have shown that these limitations can be eliminated by developing high-altitude wind power technology. Compared with near-ground wind, the advantages of high-altitude wind energy include fast speed, wide distribution, high stability, and perenniality . Meanwhile, high-altitude platforms (HAPs), situated at altitudes 17–22 km above the ground, have the capability of providing services and applications ranging from broadband wireless access, navigation and positioning systems, and remote sensing to weather observation/monitoring systems .…”
mentioning
confidence: 99%
“…A conventional wind turbine is not suitable for this application, due to its large volume and weight and the high cost of manufacturing and installation . To date, although various other prototypes have been examined to scavenge this energy, such as tethered airfoils, ladder mills, rotorcraft, and descending kites, most of them are still in early stages and more innovative approaches are required.…”
mentioning
confidence: 99%
“…22.1. Similar carousel-type configurations have been proposed for airborne wind energy [1,14]. To convert the rotational motion of the ring structure directly into electricity it can be coupled to a generator using a gear mechanism.…”
Section: System Designmentioning
confidence: 99%
“…Alternatively, single kite systems operating on single ground stations can be upscaled to increase the land use efficiency [15]. Finally, the complexity of the ground conversion can be increased, for example, using a large rotating structure (carousel) driven by several kites [14] or, alternatively, using carts that are pulled by kites on a round track [1,2].…”
Section: Introductionmentioning
confidence: 99%